The role of leukotriene B4 in early stages of experimental paracoccidioidomycosis induced in phenotypically selected mouse strains - Balderramas, Helanderson A. [UNESP]; Ribeiro, Orlando G.; Soares, Ângela Maria Victoriano de Campos [UNESP]; Oliveira, Silvio L. [UNESP] (Oxford University Press (OUP), 2013)
Paracoccidioidomycosis is a human systemic mycosis caused by the fungus Paracoccidioides brasiliensis. The mechanisms involved in innate immune response to this fungus are not fully elucidated. Leukotrienes are known to be critical for the clearance of various microorganisms, mainly by mediating the microbicidal function of phagocytes. We investigated the involvement of leukotriene B4 in the early stages of experimental paracoccidioidomycosis, which was induced by intratracheal inoculation of the fungus in selected mouse lines. The mouse lines utilized were produced through bi-directional phenotypic selection, endowed with maximal or minimal acute inflammatory reactivity, and designated AIRmax and AIRmin, respectively. AIRmax mice were more resistant to the infection, which was demonstrated by reduced lung fungal loads. However, the two lines produced similar amounts of leukotriene B4, and pharmacological inhibition of this mediator provoked similar fungal load increases in the two lines. The lower fungal load in the AIRmax mice was associated with a more effective inflammatory response, which was characterized by enhanced recruitment and activation of phagocytic cells and an increased production of activator cytokines. This process resulted in an increased release of fungicidal molecules and a diminution of fungal load. In both lines, leukotriene production was associated with a protective response in the lung that was consequent to the effect of this eicosanoid on the influx and activation of phagocytes. © 2013 ISHAM.
Keywords: Acute inflammation; Cytokines; Leukotrienes; Paracoccidioides brasiliensis; gamma interferon; icosanoid; interleukin 10; leukotriene B4; nitrous oxide; tumor necrosis factor alpha; animal cell; animal experiment; animal model; cell population; controlled study; cytokine production; fungal strain; fungal viability; fungus culture; immune response; inflammation; leukocyte; lung lavage; mononuclear cell; mouse; nonhuman; phagocyte; phase contrast microscopy; polymorphonuclear cell; South American blastomycosis; staging